Cervical spine alignment following surgery for adolescent idiopathic scoliosis (AIS): a pre-to-post analysis of 81 patients - Pepke, Wojciech; Akbar, Michael (BMC surgery, 2019)
Several studies have emphasized the importance of restoring thoracic kyphosis (TK) in the setting of AIS, but very few have discussed changes in cervical spine alignment following surgery. Aim of this study was to evaluate reciprocal cervical alignment change after modification of global and regional thoracolumbar alignment with surgery in the setting of adolescent idiopathic scoliosis (AIS).